Compostos fenólicos e capacidade antioxidante de extratos de flor de Clitoria ternatea L. - Nascimento, João Vítor do (2021)
Clitoria ternatea L. (CT) is a plant native from Tropical Asia, popularly identified in Brazil as butterfly bean. Its extracts have a wide range of pharmacological activities, in addition, CT flowers have a significant amount of phenolic compounds and anthocyanins. The general goal of this study was to evaluate the effect of ethanol concentration on the extraction of phenolic compounds from CT flower and also evaluate the antioxidant capacity by the method based on the elimination of the free radical 1,1-diphenyl-2-picrylhydrazy (DPPH) and iron reduction (FRAP). The results presented by the research demonstrated that water at room temperature proved to be the best solvent for extracting phenolic compounds from CT flowers. Among the evaluated methods of antioxidant activity, only FRAP showed a strong correlation with the concentration of total phenolic compounds. The results of this study are extremely relevant due to the capacity of bioactive extraction that could be employed in the food industry.